The potential impact of climate change on medication access and quality deserves far more attention - Warren A. Kaplan; Davidson H. Hamer; Kayoko Shioda (One Health)
Notwithstanding the obvious interconnection between humans and the world that they share with non-human inhabitants, the impact of our changing climate on certain aspects of the public health ecosystem has been under-investigated. We briefly describe some of the possible climate-induced changes in the procurement, distribution, access and use of medications, including those for animals generally and livestock specifically. A fuller understanding of the effect of climate change on medicine supply, access, use and quality, including how these affect antimicrobial resistance, would contribute to the further development of the “One Health” and “One Health Systems” concepts. We suggest that this understanding is not yet available, even though the changing incidence of infectious diseases due to changing climate has been studied. There is a need for improved understanding of the impact of extremes of humidity and heat on medication quality and research into heat-stable medicines as well as strategies for the improving resilience of the pharmaceutical supply and distribution system in complex public health emergencies caused by aberrant weather patterns.